Analysis of the implementation of green banking in achieving operational cost efficiency in the banking industry - Ika Devi Pusva; Erida Herlina (The Indonesian Accounting Review, 2017)
Green banking is a banking decision to provide banking programs or services to the only customers who consider about environmental and social impacts. The purposes of this study are to obtain empirical evidence that PT Bank Rakyat Indonesia (Persero) Tbk has implemented green banking and to find out the relationship between the implementation of green banking and the efficiency of operational cost in PT Bank Rakyat Indonesia (Persero) Tbk in the period of 2014 – 2016. This study is a qualitative research, which uses case study method for research method. The result of this study shows that BRI Kertajaya Surabaya Branch has not officially implemented green banking yet. The policy is only limited to the use of paperless program. However, based on the efficiency that is counted with operating costs and operating income (BOPO), the bank is included in a category of efficient.